Reply to “Comment on Effectiveness of a Group B Outer Membrane Vesicle Meningococcal Vaccine in Preventing Hospitalization from Gonorrhea in New Zealand: A Retrospective Cohort Study, Vaccines, 2019, 1, 5; doi:10.3390/vaccines7010005” - Janine Paynter; Felicity Goodyear-Smith; Jane Morgan; Peter Saxton; Steven Black; Helen Petousis-Harris (Vaccines, 2019)
Kenyon (2019) is correct to suggest that there is limited evidence of longer term effectiveness.[...]